Senior marks 100th birthday (Raton Range Raton, New Mexico, 1991)
Newspaper Article on the 100th birthday of Serafin Munoz.
Master list item #: 17
File location is in the Raton File Cabinet
Keywords: Munoz, Serafin; Long Term Care Facility; Raton Senior Citizens Center; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico